Antibody producing capacity to the bacteriophage phi X174 in rheumatoid arthritis. Issue 12 (December 1987) - Bucknall, R; Bacon, P; Elson, C; Jones, J V
Abstract : A study of antibody production in response to a primary immunogen, the bacteriophage phi X174, was performed in 27 patients with rheumatoid arthritis and 15 controls. All patients produced a primary (IgM) response to initial immunisation. The frequency distribution of peak antibody titres after secondary immunisation showed a marked difference between the patients and controls, with 10 patients having peak titres below 5000. The IgG component of the antibody response expressed as a percentage of total phage antibody on the 10th day after secondary immunisation was less in the patients than in the control group. There was no correlation between antibody titres and indices of disease activity, rheumatoid factor titres, or the presence of DRw4, DRw3, and DRw2. After secondary immunisation the patients with rheumatoid arthritis were treated with D-penicillamine, azathioprine, levamisole, or maintained on a non-steroidal anti-inflammatory drug. Assessment of response to tertiary immunisation again showed an impairment of antibody production in the rheumatoid group receiving non-steroidal anti-inflammatory drugs compared with the controls. None of the drugs, D-penicillamine, azathioprine, or levamisole, produced further suppression or augmentation of antibody production in response to the immunogen.